Zgodovina Medikohistorične sekcije Slovenskega zdravniškega društva - Borko, Elko (Zdravniški vestnik, 2010)
Presented is a detailed history of the Medicohistorical section of Slovenia and its activities throught 40 years, a period of time marked by the work of the presidents. The Medicohistorical section of Slovenia within the Slovenian medical association was founded in 1951 in Ljubljana. In 1963, after the demise of its first President Asst. Prof. Ivan Pintar, MD, PhD, the activities of the Section were discontinued. In 1968 the Executive Committee of the Slovenian Medical Association restored the activities of the Medicohistorical section and decided to move its headquarters to Maribor. Chief Physician Eman Pertl, MD, Section President of many years (1968-1998), described the first ten year period of its activities in detail. The second period (1979-1998) was presented by the next President Prof. Edvard Glaser, MD, PhD, who led the Section until his demise in 2007. Our paper also describes the association between the Medicohistorical Section and a related proffesional society, the Scientific society for Health Culture of Slovenia, at the time when Prof. Edvard Glaser was also the President of its Maribor branch. The report on the Section's more recent activities (1998-2007) serves to complete the overview presenting 40 years of activities of the Medicohistorical Section of Slovenia.
Keywords: health care; history; Maribor; Medikohistorična sekcija; sekcije; Slovensko zdravniško društvo; zdravniki; zdravstvo; združenja; zgodovina; zgodovina medicine